Barriers and facilitators of the electronic medical record adoption among healthcare providers in Addis Ababa, Ethiopia - Tadesse Alemu Bekele; Lemma Derseh Gezie; Herman Willems; Jonathan Metzger; Biruhtesfa Abere; Blen Seyoum; Loko Abraham; Naod Wendrad; Selamawit Meressa; Bethel Desta; Tariku Nigatu Bogale (Digital Health)
Introduction An electronic medical record (EMR) can enhance the quality of care and patient outcomes. Ethiopia started the implementation of EMR in 2013. However, its adoption among healthcare providers has been low. Thus, this study explored the barriers and facilitators of EMR adoption among healthcare providers in Addis Ababa, Ethiopia. Methods A descriptive-phenomenological approach was used. Data were collected from one hospital and three health centers from 5–13 June, 2023, that implemented the EMR. A total of 25 EMR users (physicians, health officers, pharmacists, nurses, laboratory technologists, radiology technicians) were included in the key informant interviews. The interviews were audio-recorded, transcribed verbatim, translated to English, and exported to OpenCode 4.03 software for analysis. Thematic analysis was applied to analyze, summarize, and present the data. Results Healthcare providers reported barriers operating at three levels: individual, technological, and organizational. Individual barriers included lack of digital literacy, technical knowledge, skill; motivation; and favorable attitude. Technological barriers included lack of infrastructure including computers, networks, and reliable power supply; and software-related challenges such as system downtime, lack of interoperability, comprehensiveness, and decision support systems; and system security and privacy concerns. Organizational barriers included poor quality of training, lack of follow-up, supervision and technical support; poor leadership commitment; lack of incentives and motivation; and staff turnover and workload. Perceived benefits of the system, such as ease of access to quality data, improved quality of care and work efficiency; availability of onsite technical support; presence of information technology supplies; and feedback from supervisors, were identified as facilitators of EMR adoption. Conclusion The study identified different barriers and facilitators to the adoption of the EMR. The health system should prioritize strategies to address technological, individual, and organizational factors influencing the successful adoption of the EMR to support the delivery of quality care and improve patient outcomes.